Exploring genotype–phenotype correlations in pathological myopia: a case report - Kong, Qiaoqiao; Lu, Xuejing (Frontiers in Medicine, 2025)
BackgroundGenome-wide association studies have identified key roles for specific genes in ocular axis elongation and related complications in pathological myopia (PM). In this study, we conducted a comprehensive genetic analysis of a family with a high prevalence of PM to identify novel genetic loci associated with PM, aiming to inform clinical practice.Materials and methodsGenomic DNA was extracted from oral swabs of the proband and family members for sequencing.ResultsA RHO gene variant (NM_000539.3:exon1:c.61C > T:p.R21C) was identified in the proband, potentially associated with the clinical phenotype. Her eldest sister carried the wild-type allele, while her second sister was heterozygous at the validation locus. Further investigation revealed a clustering of female patients with high myopia among the patient’s maternal siblings and their offspring. Therefore, we extended our study to include maternal relatives with axial lengths greater than 26 mm and highly myopic features to identify potential genetic loci. However, exome high-throughput sequencing did not detect any pathogenic variants. Given that the proband’s mother was deceased, whole-exome sequencing was performed on her father and her second sister, who had more severe conditions. No variants were found that could explain the observed clinical phenotype. Thus, we hypothesized that the proband’s mother might carry a gonadal chimeric variant.ConclusionThe clinical significance of the RHO gene variant (NM_000539.3:exon1:c.61C > T:p.R21C) in our family remains unclear, and the variant is classified as a variant of uncertain significance. Although this RHO variant may potentially be associated with the observed phenotype, further evidence is required to establish a definitive correlation. Based on the available data, gonadal mosaicism represents the most plausible explanatory model; however, this hypothesis cannot be considered conclusive at this stage.